Oxyberberine alleviates lipopolysaccharide-induced intestinal barrier disruption and inflammation in human colonic Caco-2 cells in vitro - Li, Cailan; Wang, Jiahao; Yang, Hongmei; Luo, Shuang; Lu, Qiang (Frontiers in Pharmacology, 2025)
BackgroundOxyberberine (OBB) is a naturally occurring isoquinoline alkaloid that is believed to possess various health-promoting properties, including anti-fungus, hepatoprotection, anti-inflammation, and anti-intestinal mucositis effects. Despite several studies reporting the health benefits of OBB in treating ulcerative colitis (UC), its specific mechanism of action has yet to be fully elucidated.PurposeThis investigation is designed to explore the potential protective efficacy of OBB and the latent mechanism using an in vitro model of UC-like inflammatory intestinal cells.MethodsCaco-2 cells were pretreated with OBB and subsequently exposed to lipopolysaccharide (LPS). The transepithelial electrical resistance (TEER), paracellular permeability, and the distribution and expression of tight- and adherent junction proteins were determined to assess barrier integrity. The levels of proinflammatory cytokines, reactive oxygen species (ROS), Nrf2, and NF-κB signaling cascade were analyzed via ELISA, qRT-PCR, immunofluorescence, or Western blotting.ResultsOBB was found to mitigate the effects of LPS on Caco-2 cell monolayers, as evidenced by the improvement in TEER and the decrease in FITC-dextran flux. Moreover, OBB ameliorated the LPS-induced decrease in the distribution and expression of several tight junction markers, including ZO-1, occludin, and E-cadherin. In addition, OBB treatment effectively inhibited LPS-induced increases in ROS, apoptosis, and Keap1 and decreases in Nrf2 and HO-1. LPS-induced elevations in nuclear NF-κB p65 and p-IκBα were suppressed by OBB. In addition, ML385, an antagonist of Nrf2, abolished the protective role of OBB.ConclusionOBB has a pronounced beneficial effect on LPS-induced damage to enteral barrier function, and the regulation of the Nrf2/NF-κB pathway is an important mechanism responsible for the protection afforded by OBB.